Circadian regulation of electrolyte absorption in the rat colon - Soták, Matúš; Polidarová, Lenka; Musílková, Jana; Hock, Miroslav; Sumová, Alena; Pácha, Jiří (American journal of physiology: Gastrointestinal and liver physiology, 2011)
The intestinal transport of nutrients exhibits distinct diurnal rhythmicity, and the enterocytes harbor a circadian clock. However, temporal regulation of the genes involved in colonic ion transport, i.e., ion transporters and channels operating in absorption and secretion, remains poorly understood. To address this issue, we assessed the 24-h profiles of expression of genes encoding the sodium pump (subunits Atp1a1 and Atp1b1), channels (α-, β-, and γ-subunits of Enac and Cftr), transporters (Dra, Ae1, Nkcc1, Kcc1, and Nhe3), and the Na(+)/H(+) exchanger (NHE) regulatory factor (Nherf1) in rat colonic mucosa. Furthermore, we investigated temporal changes in the spatial localization of the clock genes Per1, Per2, and Bmal1 and the genes encoding ion transporters and channels along the crypt axis. In rats fed ad libitum, the expression of Atp1a1, γEnac, Dra, Ae1, Nhe3, and Nherf1 showed circadian variation with maximal expression at circadian time 12, i.e., at the beginning of the subjective night. The peak γEnac expression coincided with the rise in plasma aldosterone. Restricted feeding phase advanced the expression of Dra, Ae1, Nherf, and γEnac and decreased expression of Atp1a1. The genes Atp1b1, Cftr, αEnac, βEnac, Nkcc1, and Kcc1 did not show any diurnal variations in mRNA levels. A low-salt diet upregulated the expression of βEnac and γEnac during the subjective night but did not affect expression of αEnac. Similarly, colonic electrogenic Na(+) transport was much higher during the subjective night than the subjective day. These findings indicate that the transporters and channels operating in NaCl absorption undergo diurnal regulation and suggest a role of an intestinal clock in the coordination of colonic NaCl absorption.
Keywords: intestinální absorpce; cirkadiánní proteiny Period; Enterocytes; Animals; Intestinal Mucosa; kolon; transportní proteiny; Eating; Sodium Chloride, Dietary; Intestinal Absorption; Rats, Wistar; kuchyňská sůl; Colon; elektrolyty; enterocyty; aldosteron; Circadian Rhythm; stanovení celkové genové exprese; cirkadiánní rytmus; přijímání potravy; Electrolytes; Carrier Proteins; iontové kanály; Ion Channels; Male; Aldosterone; Period Circadian Proteins; krysa rodu Rattus; zvířata; mužské pohlaví; Rats; Gene Expression Profiling; střevní sliznice; potkani Wistar